Outside Front Cover: Volume 2 Issue 1. (26th March 2021) - Gao, Jing; Zheng, Yue; Yu, Wei; Wang, Yanan; Jin, Tengyu; Pan, Xuan; Loh, Kian Ping; Chen, Wei
Abstract : Outside front cover image : The two‐dimensional (2D) ferroelectric materials are promising candidates as synaptic weight elements in neural network hardware due to their controllable polarization states and stable ferroelectricity even at the atomic scale. In this article, 2D ferroelectric semiconductor α‐In2 Se3 with coupled in‐plane and out‐of‐plane ferroelectric polarizations is used as the active channel material to emulate typical synaptic functions. Advantages like simple structure, multi‐mode operations, rich functions as well as low‐energy consumption make 2D ferroelectric materials promising for future neuromorphic applications. (DOI: https://doi.org/10.1002/smm2.1020 )